MEMBERIKAN PEMAHAMAN KEPADA SISWA MA AL ADZKAR TENTANG URGENSI HUKUM DALAM MEMBANGUN RELASI ANTARA MANUSIA DAN LINGKUNGAN MASA PANDEMI COVID-19 - Natalis, Aga; Sihotang, Amri Panahatan; Muryati, Dewi Tuti (Fakultas Hukum Universitas Semarang, 2020)
Covid-19 is a zoonosis, an animal disease that transmits to humans, the emergence of a marker of problems between humans and the environment, therefore it is important to reconcile human relations with the environment that has been damaged for centuries, due to the development of an understanding that is maintained by law due to cultural influences, religion, economic system and so on. The Community Service Team will disseminate the weaknesses of current environmental regulations that are not based on the virtues of all components of life, this is to encourage students who are policy actors to be interested and strive to create justice for all components of life, including during and after the Covid-19 pandemic through changes to existing laws. The activity was carried out at MA Al Azkar, given the lack of understanding of MA Al Adzkar students regarding the urgency of law in building relationships between humans and the environment during the Covid-19 pandemic. This community service activity is carried out through the pre-test, lecture, question and answer method, and post-test. The results of community service activities have a good impact on students because they can increase students' understanding of the urgency of the law in building relationships between humans and the environment during the Covid-19 pandemic or 64.72%.